Artificial Intelligence in Social Media - Agha, Azwar M.Q. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
The integration of artificial intelligence (AI) into social media platforms has revolutionized how individuals and organizations interact, communicate, and consume information. This literature review explores the multifaceted opportunities and challenges presented by AI in social media. It examines AI-driven technologies such as natural language processing, computer vision, and machine learning in the context of content moderation, personalized recommendations, sentiment analysis, and user engagement. In addition, the review discusses ethical concerns, including data privacy, algorithmic bias, and the potential for misinformation dissemination. By analyzing existing research and real-world applications, this paper highlights the transformative potential of AI in enhancing social media experiences while emphasizing the need for responsible and transparent AI development. The review concludes with perspectives on future trends, such as the rise of generative AI and its implications for content creation and authenticity